A novel APOC2 gene mutation identified in a Chinese patient with severe hypertriglyceridemia and recurrent pancreatitis. Issue 1 (December 2016) - Jiang, Jingjing; Wang, Yuhui; Ling, Yan; Kayoumu, Abudurexiti; Liu, George; Gao, Xin
Abstract Background The severe forms of hypertriglyceridemia are usually caused by genetic defects. In this study, we described a Chinese female with severe hypertriglyceridemia caused by a novel homozygous mutation in the APOC2 gene. Methods Lipid profiles of the pedigree were studied in detail. LPL and HL activity were also measured. The coding regions of 5 candidate genes (namely LPL, APOC2, APOA5, LMF1, and GPIHBP1) were sequenced using genomic DNA from peripheral leucocytes. The ApoE gene was also genotyped. Results Serum triglyceride level was extremely high in the proband, compared with other family members. Plasma LPL activity was also significantly reduced in the proband. Serum ApoCII was very low in the proband as well as in the heterozygous mutation carriers. A novel mutation (c.86A > CC) was identified on exon 2 of the APOC2 gene, which converted the Asn codon at position 29 into Ala, followed by a termination codon (TGA). Conclusions This study presented the first case of ApoCII deficiency in the Chinese population, with a novel mutation c.86A > CC in the APOC2 gene identified. Serum ApoCII protein might be a useful screening test for identifying mutation carriers.